Rubber-Like Materials: Strain Rate Effects - Vahap VAHAPOĞLU (Pamukkale University Journal of Engineering Sciences, 2010)
For rubber-like materials the mechanical behavior is strongly dependent on strain rate. Many of the deformation process for rubber-like materials are occurred at higher strain rate than applicable strain rate at conventional testing machine. For this reason, mechanical properties which are obtained from conventional testing machines can not be used for higher strain rate applications. So, operating strain rate for rubber-like materials must be known and mechanical properties of materials must be determined at this strain rate. This situation, especially, is important for mathematical modeling of rubber-like materials. In this study, firstly, experimental techniques and equipment employed for determining the mechanical behavior of rubber-like materials at different strain rates in tensile and compressive loading are presented. After then experimental studies of rubber-like materials for different strain rates in literature are reviewed. Experimental studies are separated as quasi-static, dynamic-low, dynamic-high and high velocity impact.